2016
DOI: 10.1111/ctr.12840
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group antigen mismatch has an impact on outcome after allogeneic peripheral blood stem cell transplantation

Abstract: ABO blood group antigen incompatibility (ABO mismatch) is not an obstacle to allogeneic stem cell transplantation (allo-SCT). However, the impact on clinical outcome after allo-SCT remains controversial. We analyzed 512 patients after allogeneic peripheral blood SCT (allo-PBSCT) for an association of ABO mismatch with transfusion requirements, myeloid and platelet engraftment, the incidence of GvHD, relapse, transplant-related mortality (TRM), and overall survival (OS). A total of 260 patients underwent ABO-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…While most TA-TMA is mediated by complement, rare patients can instead have a process driven by autoantibodies, typically to Complement Factor H (CFH), a negative regulator of the alternative pathway (31). It is also thought that other recipient-specific autoantibodies against class II HLA-molecules or other endothelial proteins may be involved (13, 32). One potential clue to this rare occurrence may be a sudden rise in B cell numbers on lymphocyte phenotyping or other autoimmune manifestations.…”
Section: Investigations At First Clinical Suspicion Of Ta-tmamentioning
confidence: 99%
See 1 more Smart Citation
“…While most TA-TMA is mediated by complement, rare patients can instead have a process driven by autoantibodies, typically to Complement Factor H (CFH), a negative regulator of the alternative pathway (31). It is also thought that other recipient-specific autoantibodies against class II HLA-molecules or other endothelial proteins may be involved (13, 32). One potential clue to this rare occurrence may be a sudden rise in B cell numbers on lymphocyte phenotyping or other autoimmune manifestations.…”
Section: Investigations At First Clinical Suspicion Of Ta-tmamentioning
confidence: 99%
“…Blood group A and B antigens are expressed on endothelial cells and may serve as targets of attack in the setting of HCT from minor ABO-mismatched donors. Many reports suggest that minor ABO mismatch is a risk factor for TRM (32, 42), and this may at least partially driven by increased TA-TMA (40, 43, 44). The use of ABO-incompatible platelets was noted to be a risk factor for the development of SOS (45) though to date this question has not been carefully studied in TMA.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Several studies showed an association between sex mismatch and viral reactivations [9] or the occurrence of GvHD, especially in the combination of a female multiparous donor and a male recipient [10]. Also, some authors suggest a higher risk of infections for ABO blood group antigen incompatible allo-HSCT [11].…”
Section: Introductionmentioning
confidence: 99%
“…Grube et al showed that ABO blood group mismatch has a significant impact on the outcome. Moreover, they found that minor-A and minor-AB ABO-mismatch represent a risk factor for increased transplant-related mortality after allo PBSCT 46 . Bolan in a study showed that hemolysis due to minor mismatched HSCT can be life-threatening and difficult to diagnose.…”
Section: Discussionmentioning
confidence: 99%